Highly Reliable Data Distribution Service Model BasedHighly Reliable Data Distribution Service Model Based on Multithreaded Worker - ZHENG Jia-cheng; ZHANG Ya-nan (Journal of Harbin University of Science and Technology)
A multi-threaded data distribution model is proposed to reduce the packet loss rate caused by slow subscribers and slow connections in traditional data distribution services. Based on the actor model, the multi-threaded worker is introduced to enable subscribers to receive data in parallel and to improve the slow connection problem caused by lack of status message from subscribers to publishers, and a highly reliable data distribution service model based on the multi-threaded worker is established to reduce the packet loss rate during data transmission effectively. A contrast experiment ZeroMQ (zero message queue) shows that the model can effectively reduce the packet loss rate when receiving messages of different lengths. The effectiveness of the model in reducing packet loss is also verified through stress tests.